Climate Change Adaptation in South Korea Environmental Politics in the Agricultural Sector - Schäfer, Susann (transcript Verlag, 2015)
Climate change will impact ecosystems and production processes. Thus, adaptation to climate change has become a prevalent concept in environmental politics worldwide. In South Korea, climate change is expected to be above the global average. As response, the South Korean government has initiated climate change adaptation in diverse sectors.In this book, the entire process, from formulation and development, implementation and reaction of involved people is examined in a particular sector, agriculture. Theoretically framed as an Actor-Network, this study highlights current developments of South Korean politics, the tensions of urban-periphery development, and the status of agriculture
Keywords: Agriculture; Politics; Asia; Nature; Human Ecology; Environmental Sociology; Geography; Environmental Policy; Adaptation; South Korea; Actor Network Theory; Landwirtschaft; Anpassung; Regionalentwicklung; Umweltpolitik; Klimaänderung; Südkorea